If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -8 = 6 + f Reorder the terms: -8 + 3f = 6 + f Solving -8 + 3f = 6 + f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1f' to each side of the equation. -8 + 3f + -1f = 6 + f + -1f Combine like terms: 3f + -1f = 2f -8 + 2f = 6 + f + -1f Combine like terms: f + -1f = 0 -8 + 2f = 6 + 0 -8 + 2f = 6 Add '8' to each side of the equation. -8 + 8 + 2f = 6 + 8 Combine like terms: -8 + 8 = 0 0 + 2f = 6 + 8 2f = 6 + 8 Combine like terms: 6 + 8 = 14 2f = 14 Divide each side by '2'. f = 7 Simplifying f = 7
| 7x^2+2x-13=0 | | 5sqrt(4x^10y^11z^8)*5sqrt(16xy^3z^3)= | | 3s+2=5s+8 | | x+.85x=245 | | 2x-3x=40 | | h=16t^2+50t+5 | | -13+2x=-39+1x | | 38-3x=-10 | | .5n=n+5 | | -50a/50=54/-50 | | c^2-9c+14= | | -1x=-33 | | f(12)=60-2/3r | | Y=1.8666Ln(x)+90.385 | | 30-2x=9-9x | | 300=25x | | 30x-2x=9-9x | | 6x+-8=16+10x | | 0.3p/-p | | 3-2x+4x+6= | | 25A=5 | | 2x/x-3=9/x-7 | | 5c-4-3c+1=8c+2 | | 5x+3=6x+17 | | 48x+48=0 | | 3x-2=4(x+5) | | 6x+32=16x-8 | | 15y+5=5 | | 2x^2+19xy+24y^2=0 | | 16x^2-4x^4=0 | | 13x+32=16x-48 | | 15+x=1 |